PENERAPAN PEMBUKUAN SEDERHANA PADA PELAKU UMKM DI DESA TOAPAYA UTARA - Andreas Putranta Sitepu; M. Isa Alamsyahbana; Bambang Sambodo; Risgar Friassantano; Ranat Mulia Pardede (Bajang Institute, 2025)
Micro, Small, and Medium Enterprises (MSMEs) played an important role in both local and national economies. However, most MSME actors in Toapaya Utara Village, such as Setia Rasa Snack & Catering, Feni Fino, and Cabe Pak Suliah, did not understand the importance of simple bookkeeping for managing their business finances. The objective of this community service program was to enhance the understanding of MSME actors regarding simple bookkeeping through stages of surveys, implementation, monitoring, and evaluation. The results showed that MSME owners began to understand how to record financial transactions regularly, distinguish between business and personal funds, and recognize the significance of bookkeeping in supporting business sustainability. This training was expected to help MSME actors manage their business finances more effectively and support the development of their businesses in the future.